2013
DOI: 10.1097/acm.0b013e3182a34b1e
|View full text |Cite
|
Sign up to set email alerts
|

Validity Evidence for a Patient Note Scoring Rubric Based on the New Patient Note Format of the United States Medical Licensing Examination

Abstract: There is initial validity evidence for use of this rubric to score local clinical exams that are based on the new USMLE patient note format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…In response to this change, the University of Illinois updated the patient note format used in its graduation competency exam (GCE) to mirror that of the USMLE and developed a rubric to score the new note format. Initial validity evidence for that rubric was reported by Park et al 10 The purpose of the present study was to obtain additional validity evidence for the UIC patient note rubric by investigating the psychometric characteristics and curricular implications of the diagnostic justification scores in the context of the USMLE 2012 format for the postencounter notes.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In response to this change, the University of Illinois updated the patient note format used in its graduation competency exam (GCE) to mirror that of the USMLE and developed a rubric to score the new note format. Initial validity evidence for that rubric was reported by Park et al 10 The purpose of the present study was to obtain additional validity evidence for the UIC patient note rubric by investigating the psychometric characteristics and curricular implications of the diagnostic justification scores in the context of the USMLE 2012 format for the postencounter notes.…”
Section: Discussionmentioning
confidence: 96%
“…10 We found that scoring the new diagnostic justification task of the patient note had benefits for both the student assessment and curriculum evaluation functions of our GCE. The item analysis indicated that of the four tasks in the patient note (Documenting the history and PE, DDx, Justification, and Workup), the justification task was the most predictive of overall GCE performance and provided unique information about students' clinical reasoning abilities.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Success is measured by clinician satisfaction, percent adoption, and note length or timing; note quality is judged using a checklist derived from professional surveys. [5][6][7][8][9][10][11][12][13][14][15] End points like these will often make 1 document look better than another in a "results" section, but it is the relation between communication strategies and healthcare outcomes that determines whether 1 approach or another is of benefit to the patient.…”
mentioning
confidence: 99%